ANALISIS SWOT DALAM MENENTUKAN STRATEGI PENGEMBANGAN USAHA TERNAK ITIK PETELUR PERSEPEKTIF BISNIS ISLAM - Fasihul Lisan; Mabruroh Munib (IZZI: Jurnal Ekonomi Islam, 2024)
The poultry industry is the main trigger for national development in the livestock sub-sector. One of the businesses that the community is involved in is laying duck farming. Laying duck farming business has good prospects for development, both as a main business and as a side business, such as duck farming. Mr. Mil, who is located in Bulu Village, Kraksaan District, Proboliggo Regency with an intensive maintenance system. The purpose of this research is to analyze the development of Mr. Mil's laying duck business which is located in Bulu Village, Kraksaan District, Proboliggo Regency. The research was conducted using the SWOT analysis method while the data collection technique was by conducting interviews and observation. In terms of data sources, additional material comes from written sources, namely documents and journals. The results showed that alternative strategies that can be applied in business development are increasing production capacity through adding cages, having relationships with more than one agent and retailer, making maximum use of technology, building cooperation with local government agencies or governments, observing the maintenance of ducks from climate and unstable weather, Utilizing alternative feeds to overcome duck feed, Increasing promotions by utilizing social media, Adding distribution channels.